2018
DOI: 10.1055/s-0037-1621710
|View full text |Cite
|
Sign up to set email alerts
|

Fibrolamellar Carcinoma: Recent Advances and Unresolved Questions on the Molecular Mechanisms

Abstract: Fibrolamellar hepatocellular carcinoma (FLC) is a rare form of primary liver cancer that affects adolescents and young adults without underlying liver disease. Surgery remains the mainstay of therapy, however most patients are either not surgical candidates, or suffer from recurrence. There is no approved systemic therapy and the overall survival remains poor. Historically classified as a subtype of Hepatocellular carcinoma (HCC), FLC has a unique clinical, histological and molecular presentation. At the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 71 publications
(105 reference statements)
0
53
0
3
Order By: Relevance
“…2 Although FLHCC was usually referred as a subtype of HCC, recent researches have demonstrated that FLHCC is actually an independent entity, with distinctive molecular tumor profile, histological features and clinical presentation. 3,4 One of the most feared complications associated with FLHCC is the development of acute onset hyperammonemic encephalopathy (HAE), which was first reported by Sethi et al 5 in 2009, this condition is associated with high mortality. 6 High mortality was related to the ignorance of the physiopa-thology of HAE in patients with FLHCC.…”
Section: Dear Editormentioning
confidence: 99%
“…2 Although FLHCC was usually referred as a subtype of HCC, recent researches have demonstrated that FLHCC is actually an independent entity, with distinctive molecular tumor profile, histological features and clinical presentation. 3,4 One of the most feared complications associated with FLHCC is the development of acute onset hyperammonemic encephalopathy (HAE), which was first reported by Sethi et al 5 in 2009, this condition is associated with high mortality. 6 High mortality was related to the ignorance of the physiopa-thology of HAE in patients with FLHCC.…”
Section: Dear Editormentioning
confidence: 99%
“…FLHCC is a rare liver cancer that predominantly affects adolescent and young adults with no history of liver disease (Craig et al, 1980; Eggert et al, 2013; Honeyman et al, 2014; Kakar et al, 2005; Lalazar and Simon, 2018; Torbenson, 2012). It does not respond well to chemotherapy and the overall five year survival rate of FLHCC patients is only 30-45% (El-Serag and Davila, 2004; Kakar et al, 2005; Katzenstein et al, 2003; Lim et al, 2014; Mavros et al, 2012; Weeda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances in the molecular characterization of FLC revealed potential targets including the mTOR pathway or Aurora A kinase. However, even with favorable outcome of mTOR inhibition in single patients [18], no promising results have been published from controlled trials to date [4]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the epidemiology and etiology of FLC differs substantially from typical HCC as the majority of FLC cases are diagnosed in younger patients (< 40 years of age) and are not associated with underlying liver disease. Additionally, recent studies indicate that the biology of FLC differs from typical HCC [1-3] and a DNAJB1-PRKACA fusion transcript has been identified as the signature genetic event in the tumor development of FLC [2, 4]. While several studies indicate that the 5-year survival of patients with FLC (34–70%) is better than for typical HCC (10–16%) [5-7], this difference seems to be mainly attributable to the absence of cirrhosis in most FLC cases [8, 9].…”
Section: Introductionmentioning
confidence: 99%